Future Heat-Related Mortality in Türkiye: Projections Under CMIP6 Scenarios Towards National Climate Action Targets - Yılmaz, Merve; Tayanç, Mete; Toros, Hüseyin; Can, Günay (Springer Science and Business Media LLC, 2025)
Climate change associated with higher temperatures and more frequent/stronger heat waves has been causing adverse health effects and increasing vulnerability in the mega-city of & Idot;stanbul. To adapt to climate change and extreme heat, it is crucial to consider the associated health risks. This study aims to estimate current and future mortality risks associated with high summer temperatures in & Idot;stanbul. Using data from 2013 to 2017, mortality risks and total attributable mortalities during the summer period were predicted for mid-century (2053-2057) and end-century (2093-2097) under various SSP climate scenarios. Daily maximum temperatures were correlated with daily deaths using a distributed lag non-linear model to estimate relative risks. Future temperatures were projected using recent climate models (CMIP6-GCM), with an average taken from eight models using a multi-model ensemble approach. Statistical downscaling and calibration with observation data were applied, with quantile delta mapping (QDM) providing the most accurate bias-correction. Compared to the reference period, average extreme temperatures in summer months (June-July-August) are expected to remain almost constant (34 degrees C) until mid-century (over the entire period 2015-2050), while end-of-century extreme temperatures are projected to increase by 1.2 degrees C (-0.4-3.4 degrees C) under SSP1-1.9 and 6.6 degrees C (3.1-11 degrees C) under SSP5-8.5. Future attributable mortality rates in summer are projected to rise by 15.6% (95% CI: 0.4-37.2%) in 2053-57 and 38.0% (95% CI: 3.7-63.3%) in 2093-97 under SSP5-8.5. Achieving T & uuml;rkiye's net zero emission target by 2053 (SSP1-1.9) and implementing adaptive policies could reduce the expected attributable deaths for summer months in & Idot;stanbul by 39.7%, from 15,732 mid-century to 9,482 by end-century. By recognising these risks, policymakers can more effectively anticipate and mitigate the impacts of extreme heat on urban populations.Graphical Abstract To address the predicted impacts of climate change, T & uuml;rkiye has implemented several climate action initiatives, including Climate Change Adaptation Strategy and Action Plan (2024-2030), Climate Change Mitigation Strategy and Action Plan (2024-2030), & Idot;stanbul Climate Change Action Plan, and a national commitment to achieving net-zero greenhouse gas emissions by 2053. The impact of rising temperatures on mortality risks in & Idot;stanbul is examined in this study by using the latest climate projections, CMIP6-GCM models and SSP scenarios. A health impact model is employed using distributed lag non-linear models (DLNM) to estimate attributable mortality rates when temperatures exceed the minimum mortality threshold. Findings indicate that the maximum daily temperatures are expected to rise significantly under different climate scenarios, especially with the highest emissions pathway (SSP5-8.5) resulting in the most extreme warming. Compared to the historical (1980-2014) period, extreme temperatures at the end-of-century are projected to increase by 1.2 degrees C (-0.4-3.4 degrees C) under SSP1-1.9 and 6.6 degrees C (3.1-11 degrees C) under SSP5-8.5. During the reference period, 4,009 deaths in & Idot;stanbul were linked to extreme heat. By the end of the century, projections estimate 9,482 deaths under the optimistic SSP1-1.9 scenario and 39,779 under the pessimistic SSP5-8.5. Achieving net-zero emissions by 2053 could reduce mid-century deaths from 15,732 to 9,482 by 2100- a 39.7% decline. However, even under SSP1-1.9, the mortality rate is projected to increase by 4. 5% compared to 2013-2017 due to population growth. Therefore, while emission reductions are essential, adaptation strategies, such as managing urban populations and strengthening climate resilience of the cities, are equally vital to protect public health.
Keywords: Future health risk; Istanbul; Extreme summer heat; SSP scenarios; Attributable mortality; Climate projection